Comparison of various culture media effectiveness in the isolation of bacteria from Pekan peat swamp forest soil - Ghazali, Noor Nazihah; Mohamad Khairul Adilah, Mohamad Mukhlis; Zainal Abidin, Zaima Azira; Mohd Omar, Suhaila (Malaysian Society for Microbiology, 2016)
Aims: Previously described as non-favorable-microbial habitat, peat swamp forest has its own features, which are extremely acidic, poor in nutrient, water-logged and anoxic environment where rate of decomposition of plant litters is quiet slow. Interestingly, current research has proven that there is diversity of microbial communities in this ecosystem. The main objective of this study is to isolate bacteria from Pekan peat swamp forest soil that play a role in the decomposition of plant litters through cultivation on different agar-based medium. The success of isolation of bacteria from this neglected habitat could open the opportunity in unleashing the specific role of bacteria in peat swamp plant litter degradation as well as potential biotechnological application of these bacteria in lignocellulose-related industry. Methodology and results: To mimic the peat condition that is low in nutrient and comprised of plant debris, M1 and peat agar supplemented with cellulose, glucose, lignin and xylan were used. Specifically, for the isolation of actinomycetes, dry and wet heat pre-treatments were applied to the soil samples. Then, the samples were cultivated on three different agars which were oatmeal agar as well as M1 and peat agar supplemented with glucose. Enrichment method was applied in the isolation of cellulase-producing bacteria. It was found that higher number of bacteria and actinomycetes were successfully isolated from peat agar, followed by oatmeal agar and M1. In fact, more actinomycetes were isolated from soil that was treated with wet heat pre-treatment compared to dry heat pre-treatment and on peat agar compared to M1 and oatmeal agar. This finding is promising, indicating that the application of peat water in the agar-based medium is useful to mimic the actual environment of peat swamp and increase the possibility to isolate indigenous bacteria. Primary screening of isolates from samples enriched with carboxymethyl cellulose (CMC) showed positive result of decolourisation zone on Azo-CM-Cellulose agar indicating the ability of isolates to degrade cellulose compound. Conclusions, significance and impacts of study: The study indicates the effectiveness of different culture media in successful isolation of bacteria including actinomycetes. Using the enrichment method, bacteria that are able to degrade cellulose compound was successfully isolated even though it is well known that plant litter degradation in the peat swamp environment happens at very slow rates.